PENINGKATAN PEMAHAMAN IBU HAMIL TENTANG PENANGANAN ANEMIA PADA KEHAMILAN DI DESA JEMPONG BARU WILAYAH KERJA PUSKESMAS SEKARBELA KOTA MATARAM - Dian Soekmawaty Riezqy Ariendha; Irni Setyawati; Kusniyati Utami; Hardaniyati Hardaniyati; Yesvi Zulfiana (Jurnal LENTERA, 2022)
Anemia has a very negative effect, especially for babies in the womb, including itcan cause miscarriage, babies born not quite months, babies are not fullydeveloped, bleeding during childbirth, irregular contractions, disruption during thedelivery process and susceptibility to infection can even result in a lack ofproduction of breast milk. Aim of community services is to improve knowledgeabout prevention of anemia. Methods: The implementation of community serviceactivities is carried. Results: pregnant women who attended were veryenthusiastic, after processing the questionnaire before and after the provision ofhealth education, there was an increase in knowledge. Conclusion:Implementation of providing health education to increase knowledge for thecommunity with risks that may occur with the condition of the community is verynecessary to be done Apart from being an enhancer and an increase inknowledge, it is also an action to reduce the risk of health problems for thecommunity